Soil Contamination by Polycyclic Aromatic Hydrocarbons Due to Diesel Spill near Residential Homes: Health Risk Assessment - Ugochukwu, Uzochukwu C.; Ochonogor, Alfred; Jidere, Chika; Nkoloagu, Frida; Ewoh, John (Asian Journal of Chemistry, 2018)
This study assessed the human health risk of exposure to polycyclic aromatic hydrocarbons (PAHs) in a soil environment of a Nigerian city contaminated by diesel spill from a telecommunication facility. Gas chromatography-mass spectrometry was employed in analyzing the PAHs. The contaminated soil was delineated into sub-locations AA1, AA2 and AA3. A total of 477 mg/Kg of PAHs with 58 % naphthalene and 42 % carcinogenic PAHs were found in sub-location AA1 whereas the total PAHs for sub-location AA2 was 24.2 mg/kg with 53 % naphthalene and 47 % carcinogenic PAHs. No PAH contamination was detected in sub-location AA3. The assessment of health risk exposure to the non-carcinogenic PAHs indicated insignificant risk for both sub-locations AA1 and AA2. However, the assessment of carcinogenic health risks using soil toxicity method indicates that soil locations AA1 and AA2 were both toxic. The targeted chemical-specific approach reveals cancer risk of exposure to carcinogenic PAHs only in sub-location AA1.